Shotcrete prefabricated ferrocement panels by using WA mixture materials - Abushawashi, Nadim; Vimonsatit, Vanissorn; Hopkins, George (Research Publishing Services, 2012)
This report is a part of an experimental series to investigate the possibility of producing ferrocement to compete with other construction materials. The aim of this series was to explore the benefits of using the shotcrete method to fabricate ferrocement panels Shotcrete prefabrication can lead to high quality product with reduced construction time and cost. To study the constructability of ferrocement elements with reliable mix pump ability using the shotcrete method, several mix designs are considered using different sand types. All materials used are locally available in Perth Western Australia. In total, 11 Ferrocement panels, each of size 1200 mm long, 300 mm wide and 30 mm thick, were fabricated and tested to determine mix pump-ability, penetration, and strength under flexure. A pump-able mix, with full through penetration of the mortar between the mesh wires was achieved by using Gingin sand. The strength development of this mixture still is a significant part of future experiments.